AI WRITING TOOLS IN THE CLASSROOM: INVESTIGATING USAGE, CHALLENGES, AND ADAPTATIONS BY RURAL ENGLISH TEACHERS - Kamarullah, Kamarullah; Sarinauli, Barep; Syahmidi, Humaira (Universitas Muhammadiyah Metro, 2024)
This phenomenological study explores the integration of AI tools in teaching English writing in rural Central Aceh, offering insights into the educators’ challenges and adaptive strategies. Amidst the global push towards digital education, rural areas often lag behind due to infrastructural deficits and limited access to advanced technological resources. This study aims to understand how AI tools are being utilized by teachers in such contexts to improve English writing skills. Conducted through semi-structured interviews with three high school teachers, the study employs a thematic analysis to uncover how educators navigate the complexities of using AI tools like ChatGPT, Grammarly, and Quillbot under constrained conditions. Key challenges identified include limited technological infrastructure, absence of formal training, and diverse student proficiency with technology. Despite these challenges, teachers have adopted innovative strategies such as shared computer time, collaborative learning, self-learning initiatives, and leveraging community support networks. The findings highlight the resilience and adaptability of educators in underserved regions, suggesting that enhancing technological infrastructure, providing targeted professional development, and developing user-friendly AI tools are crucial for bridging the educational divide. The study calls for a balanced approach to integrating AI in education, ensuring that it complements traditional teaching methods and fosters inclusive learning environments.